2019
DOI: 10.1039/c8cp06171h
|View full text |Cite
|
Sign up to set email alerts
|

Morphology evolution of magnesium facets: DFT and KMC simulations

Abstract: One of the crucial steps for the development of batteries is understanding the interface stability and morphological changes occurring during continuous stripping and deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 72 publications
4
17
0
Order By: Relevance
“…As shown in Figure 3, the magnesium deposited at 0.5 mA/cm 2 on copper preferentially grows along the (1 0 1) crystal plane for both electrolytes, which is the plane with the highest surface area fraction (Lautar et al, 2019). This observation suggests that the interactions between the electrolyte and the metal are more favorable.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As shown in Figure 3, the magnesium deposited at 0.5 mA/cm 2 on copper preferentially grows along the (1 0 1) crystal plane for both electrolytes, which is the plane with the highest surface area fraction (Lautar et al, 2019). This observation suggests that the interactions between the electrolyte and the metal are more favorable.…”
Section: Resultsmentioning
confidence: 95%
“…Recently there has been interest in magnesium deposition and how deposition kinetics can influence the resultant morphology (Viestfrid et al, 2005; Matsui, 2011; Wetzel et al, 2015; Crowe et al, 2017). Early magnesium battery research suggested that it is unfavorable for magnesium to form dendrites, unlike lithium metal; this is attributed to differences in the crystal structures of each metal (Ling et al, 2012; Jäckle and Groß, 2014; Lautar et al, 2019). Although magnesium is less likely to form dendrites compared to lithium, dendritic magnesium deposits been observed with both complex and simple salt electrolytes (Ding et al, 2018; Davidson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55] The applied potential is varied through the addition of surface charges (positive or negative) which are counterbalanced by a homogeneous background charge to account for the electrical double layer response, following the method used in previous works (see Supplementary Information S1 for details). 53,[55][56][57][58][59] For solid electrodes, the surface tension for a given -surface is the work required to form a unit area of surface by cleaving the bulk, and its related free electrochemical energy, can be directly extracted from DFT calculations, and linked to the surface tension through the relation:…”
Section: Methodsmentioning
confidence: 99%
“…For reductive potentials at which all remain positive, the increase of the (0001) fraction induces a flattening of the particle shape as experimentally observed. 59 At = +2.42V/Mg over-potential, the {0001}-class consisting in only two (0001) and (000 ) surfaces reaches the critical surface tension. The increase of one surface area necessarily leads to the increase of the other one, which results in the formation of thinner and thinner hexagonal platelets (Fig.…”
Section: Electrode and Magnified In The Potential Region Of Interest (Reductive Conditions ) The Green Blue And Red Domains Define The Pomentioning
confidence: 99%
“…Homogenous plating of magnesium was explained by Jäckle et al [79] who suggested that barriers of terrace surface diffusion and interlayer surface diffusion could be a descriptor of metallic deposition morphologies. Following this work, Kopac Lautar et al [80] examined all possible surfaces in the magnesium metal crystal and they showed that the energetically most favorable surface [0001] supports homogenous plating while migration barriers on some other crystal planes are more in favor for non-homogenous plating. Considering high current density we can expect that also other crystal planes would be energetically favorable, leading to the formation of non-uniform magnesium deposits or even dendrites [76][77][78].…”
Section: Metallic Magnesium Anodementioning
confidence: 99%